The Role of Code-Switching in Enhancing Learners' Understanding of Social Sciences in the Mopani East District, Lulekani Circuit, Limpopo Province, South Africa - Nkuna, Amon; Molise, Habasisa; Segooa, Mapule (Journal of Posthumanism, 2026)
This qualitative case study examines the impact of code-switching on learners' understanding of Social Sciences concepts in Grade 7 classrooms in the rural Mopani East District of Limpopo Province, South Africa. Rooted in the interpretivist paradigm, the study aims to explore the lived experiences and perceptions of both teachers and learners concerning the use of code-switching during classroom instruction. A case study focusing on the role of code-switching was conducted, guided by grounded theory. Participants were intentionally selected to take part in the study, consisting of 4 social sciences educators and 4 Grade 7 learners from a class of 44 learners and 9 educators. Each group included 8 participants. Data collection involved semi-structured interviews and observations. All data were analyzed using thematic analysis. The results showed that code-switching acts as a bridge connecting learners who felt disconnected from their teachers in the classroom due to language barriers. Additionally, the findings indicated that code-switching helps learners become more engaged during lessons. The researcher concluded that code-switching is vital in content subjects as it boosts learners’ participation in class. The study recommends that the school, along with the SGB and community, consider the needs of the school when developing language policies. Finally, educators should practice code-switching when appropriate during lessons.